ANALISIS KEPUASAN PENGUNJUNG TERHADAP DAYA TARIK WISATA TERSERTIFIKASI CHSE (STUDI KASUS CANDI BOROBUDUR) - Ananti, Deni Dwi; Asyarief, Ernova Rizki (Kepariwisataan: Jurnal Ilmiah, 2023)
The purpose of this study was to determine the application of CHSE in Borobudur Temple, to determine the level of visitor satisfaction when visiting a CHSE-certified Tourist Attraction, and to determine visitor confidence in CHSE certification at Borobudur Temple. The method used is a mixed method with Importance Performance Analysis (IPA). The data technique used observation, questionnaires and interviews with managers. The results of this study indicate that the implementation of CHSE at Borobudur Temple with its available management, checking the temperature before entering the area, implementing non-cash payments, implementing non-cash payments, warning warnings, waste management systems, and maintaining cleanliness with a zoning system. The level of visitor satisfaction with the CHSE certification reached 92.76 which is in line with expectations and based on the analysis of the Important Performance Analysis chart and 51% of respondents said CHSE is very important in a visit to a tourist attraction.